A Comprehensive Quality-of-Life Instrument for Aesthetic and Functional Rhinoplasty: The RHINO Scale. Issue 2 (February 2016) - Lee, Matthew K.; Most, Sam P.
Abstract : Background: Currently, there is no validated quality-of-life instrument that evaluates both functional and aesthetic outcomes after rhinoplasty. The goal of this study was to develop and validate a comprehensive quality-of-life instrument to assess patient satisfaction with both functional and aesthetic outcomes after rhinoplasty. Methods: The study was designed as a prospective instrument validation study at a university-affiliated academic medical center. Inclusion criteria included patients with nasal obstructive symptoms, nasal aesthetic deformity, or both, who underwent functional and/or aesthetic rhinoplasty by a single surgeon between December 2014 and June 2015. A novel 10-item instrument (the Rhinoplasty Health Inventory and Nasal Outcomes [RHINO] scale) was developed to assess physical, mental, and social well-being after functional and/or aesthetic rhinoplasty. Instrument validation was performed by assessment of test–retest reliability, internal consistency reliability, construct validity, and concurrent validity. Results: Twenty-two patients (10 males and 12 females) were enrolled. Mean age was 34.9 years (range: 18–67 years). All patients were followed for a minimum of 12 weeks (range: 12–23 weeks; mean: 16.5 weeks). Mean RHINO score was 51.4 ± 13.8 on the first preoperative evaluation and 51.7 ± 12.5 when repeated preoperatively on the day of surgery ( r = 0.94; P < 0.001). Internal consistency demonstrated Cronbach's α value of 0.74. Mean postoperative RHINO score was 84.7 ± 14.1 (mean difference from preoperative RHINO = 33.2 ± 18.9; P < 0.001). Conclusions: The RHINO instrument demonstrates robust reliability and validity in assessing patient-reported satisfaction with rhinoplasty outcomes.